KEPRIBADIAN PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Samsul Riza; Hemawati (Jurnal At-Tabayyun, 2020)
Personality is a term that is no stranger to being heard especially in the discipline of the world of education. Because in its own purpose education is seen as an effort in forming a better personality. The familiarity of the term "personality" is often seen as commonplace to be used in a variety of simple expressions in everyday life. Tujannya this research to find out the personality of the perspective of islamic philosophy of education and how it is formation in Islam as well as the concept of human and personal traits of Muslims. The research methods used in this research are qualitative methods, with descriptive analysis. Describes the personality perspective of the Islamic Philosophy of Education and how it was formation in Islam as well as the concept of human and personal qualities of Muslims. The results showed that the substance of personality consists of several criteria, namely the personality of an organic structure, personality is a trait or behavior displayed by humans, that there is a relationship between the two, actions and impulses from within, and behavior displayed in everyday life. Personality is the result of a process of life that a person lives. Because the process experienced by each person is different, the personality of each individual is different. There is no common personality between two individuals, even if a twin brother is from one egg. As for the personality of Muslims is not to look insulted to others, must not be bad and must not also lurk around the mistakes of others, love of unity, trust, not hasad (envy), not arrogant and arrogant, do not seek the disgrace of others, be fair and hate persecution, hate bribery, hate false testimony, strengthen the ropes of friendship, love of science, Good with neighbors, like to help and attach importance to others.